Biofertilizers in the control of Pratylenchus brachyurus in soybean crop (Research, Society and Development, 2022)
Nematodes are of great importance in soybean cultivation, especially the Pratylenchus brachyurus known as root lesion nematode. Its attack on plant roots causes less efficiency in the absorption of water and nutrients, in addition to damaging the plant's development. There is still no fully efficient method to control this phytopathogen, however, some products are available on the market, including biological control. Thus, the aim of this study was to evaluate commercial biological products in the efficiency of reducing the nematode population in soybean crop in Goiás, Brazil. The design was completely randomized in a 2x4 factorial scheme, the first factor being two soybean genotypes (Brasmax Bônus and Nidera NS 8383) and the second factor the treatments consisting of different dosages in an association of three commercial products: No-Estio®, Bio-fertility® and Radic®. The treatments used were: T1 control - without application of the products; T2 half the recommended dose; T3 the recommended dose and T4 a dose and a half that recommended by the manufacturer. Plant evaluation was carried out after 75 days of nematode inoculation. The results obtained showed that both cultivars hosted P. brachyurus, however, the treatments using the products had a lower population density of this nematode. It was concluded that the two soybean cultivars are hosts of Pratylenchus brachyurus. The agronomic character plant height was more affected when there was no application by the biological method. The association of No-Estio®, Bio-fertility® and Radic® products reduced the population density of nematodes in infected plants.